Prediction of Stent-Retriever Thrombectomy Outcomes by Dynamic Multidetector CT Angiography in Patients with Acute Carotid T or MCA Occlusions - Thierfelder, K.M.; Sommer, W.H.; Ertl-Wagner, B.; Beyer, S.E.; Meinel, F.G.; Kunz, W.G.; Buchholz, G.; Reiser, M.F.; Janssen, H. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: The selection of patients for endovascular therapy is an important issue in stroke imaging. The aim of this study was to determine the predictive value of 3 different dynamic CT angiography parameters, occlusion length, collateralization extent, and time delay to maximum enhancement, for latest generation of stent retriever thrombectomy recanalization outcomes in patients with acute ischemic stroke.MATERIALS AND METHODS: In this study, subjects were selected from an initial cohort of 2059 consecutive patients who had undergone multiparametric CT, including whole-brain CT perfusion. We included all patients with a complete occlusion of the M1 segment of the MCA or the carotid T and subsequent intra-arterial stent retriever thrombectomy. Dynamic CT angiography was reconstructed from whole-brain CT perfusion raw datasets. Angiographic outcome was scored by using the modified TICI scale; and clinical outcome, by using the modified Rankin Scale. Logistic regression analyses were performed to determine independent predictors of a favorable angiographic (mTICI = 3) and clinical outcome (mRS ≤2).RESULTS: Sixty-nine patients (mean age, 68 ± 14 years; 46% men) were included for statistical analysis. In the regression analysis, a short occlusion length was an independent predictor of favorable angiographic outcome (OR, 0.41; P < .05). Both collateralization grade (OR, 1.00; P > .05) and time delay to peak enhancement (OR, 0.90; P > .05) failed to predict a favorable angiographic outcome. None of the dynamic CT angiography predictors were significantly associated with clinical outcome on discharge (OR, 0.664–1.011; P = .330–.953) or at 90 days (OR, 0.779–1.016; P = .130–.845).CONCLUSIONS: A short occlusion length as determined by dynamic CT angiography is an independent predictor of a favorable angiographic outcome of stent retriever thrombectomy in patients with ischemic stroke.IVTintravenous thrombolysismTICImodified Thrombolysis in Cerebral Infarction scalespCTAsingle-phase CT angiographyWB-CTPwhole-brain CT perfusion